40CrMoV13.9 notched specimens under multiaxial fatigue: an overview of recent results - S.M.J. Razavi; M. Peron; J. Torgersen; F. Berto; T. Welo (Fracture and Structural Integrity)
The multiaxial fatigue strength of circumferentially V-notched and semicircular notched specimens made of 40CrMoV13.9 has been investigated in this paper. The multiaxial load were applied using combined tension and torsion loading, both in-phase and out-of-phase. The axissymmetric V-notched specimens were characterized by a blunt notch tip (radius: 1 mm) and notch opening angle of 90o and the semicircular specimens were characterized by a constant notch tip radius. The net sectional area of both cases was equal with a diameter of 12 mm. The notched specimens were tested under pure mode I (tension), mixed mode I/III and pure mode III (torsion). More than 120 fatigue test data are used in this paper to evaluate the fatigue behaviour of 40CrMoV13.9 alloy. All fatigue data are analysed using the Average Strain Energy Density (ASED) criterion which employs the mean value of the strain energy density evaluated over a finite size semicircular sector surrounding the tip of the notch to predict the fatigue life of the tested specimens.